1978
DOI: 10.1111/j.1365-2141.1978.tb03632.x
|View full text |Cite
|
Sign up to set email alerts
|

The Surface Morphology of Mitogen‐Stimulated Human Peripheral Blood Lymphocytes

Abstract: The changes occurring in surface morphology during the transformation of normal peripheral blood lymphocytes by phytohaemagglutinin (PHA) are described and the surface ultrastructure of the PHA-induced blasts is compared with that of pokeweed mitogen (PWM)-and rabbit anti-beta2-microglobulin antiserum-induced blasts. Both mitogen-specific and non-specific changes were observed and their possible relationship to the activation of lymphocyte subpopulations is discussed. Similar surface characteristics found in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1983
1983
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…It was reported that soon after human peripheral blood lymphocytes had been treated with phytohaemagglutinin (PHA), a T-cell-specific mitogen, their fairly smooth surfaces were covered by a mixture of stub-like or long conical villi, blebs or ruffles. But these surface features decreased or disappeared eventually when PHA was cleared away (Hoffman et al 1977;Newell and Roath 1978). The surface topography of the cell can reflect its function, being related to cell movement, growth, proliferation, aging, metabolism, or other functions (Ferenczy 1980;Newell 1980).…”
Section: Discussionmentioning
confidence: 97%
“…It was reported that soon after human peripheral blood lymphocytes had been treated with phytohaemagglutinin (PHA), a T-cell-specific mitogen, their fairly smooth surfaces were covered by a mixture of stub-like or long conical villi, blebs or ruffles. But these surface features decreased or disappeared eventually when PHA was cleared away (Hoffman et al 1977;Newell and Roath 1978). The surface topography of the cell can reflect its function, being related to cell movement, growth, proliferation, aging, metabolism, or other functions (Ferenczy 1980;Newell 1980).…”
Section: Discussionmentioning
confidence: 97%